Live birth rate per fresh embryo transfer and cumulative live birth rate in patients with PCOS under the POSEIDON classification: a retrospective study - Jiang, Linlin; Sun, Yiting; Pan, Ping; Li, Lin; Yang, Dongzi; Huang, Jia; Li, Yu (Frontiers in Endocrinology, 2024)
Background: Ovarian stimulation (OS) for IVF/ICSI in women with PCOS often results in multiple follicular development, yet some individuals experience poor or suboptimal responses. Limited data exist regarding the impact of poor/suboptimal ovarian response on pregnancy outcomes in women with PCOS. Objectives: To evaluate whether the live birth rate (LBR) per fresh embryo transfer and cumulative live birth rate (CLBR) per aspiration cycle differ in women with PCOS defined by the POSEIDON criteria. Method: A retrospective study involving 2377 women with PCOS who underwent their first IVF/ICSI cycle at Sun Yat-Sen Memorial Hospital from Jan 2011 to Dec 2020. Patients were categorized into four groups based on age, antral follicle count, and the number of oocytes retrieved, according to the POSEIDON criteria. The LBR and CLBR were compared among these groups. Logistic regression analysis was performed to assess whether the POSEIDON criteria served as independent risk factors and identify factors associated with POSEIDON. Results: For patients <35 years old, there was no significant difference in the clinical pregnancy rate between POSEIDON and non-POSEIDON patients, whereas POSEIDON patients exhibited lower rates of implantation and live birth. POSEIDON Group 1a displayed lower rates of implantation, clinical pregnancy and live birth. However, no significant differences were observed in the rates of clinical pregnancy and live birth between POSEIDON Group 1b and non-POSEIDON Group. For patients ≥35 years old, there were no significant differences in the rates of implantation, clinical pregnancy, and live birth between POSEIDON and non-POSEIDON patients. CLBRs were significantly lower in POSEIDON Group 1 and 2, compared with the non-POSEIDON groups. The levels of BMI, FSH and AFC were associated with POSEIDON hypo-response. POSEIDON was found to be associated with lower CLBR, but not LBR per fresh embryo transfer. Conclusion: In patients with PCOS, an unexpected suboptimal response can achieve a fair LBR per fresh embryo transfer. However, CLBR per aspirated cycle in POSEIDON patients was lower than that of normal responders. BMI, basal FSH level and AFC were independent factors associated with POSEIDON. Our study provides data for decision-making in women with PCOS after an unexpected poor/suboptimal response to OS.